Changes in Mollusc Species Composition in the Mining Landscape on the Exemple of the Extinct Pond System Territory - Kupka, Jiří; Švehláková, Hana; Kašovská, Kamila (GeoScience Engineering, 2013)
The development of the industry in last two centuries, and especially intensive coal mining activities definitely changed the local landscape character. It led to the destruction of indigenous biotopes with natural flora and fauna communities. Many ecological studies use a group of molluscs as indicators of changes in the landscape. The advantage of this group is a relatively small number of taxa, relatively simple determination and very good knowledge of ecological requirements and distribution of individual species. The territory of Loucké ponds represents an interesting area in the industrial landscape of Karvinsko, where based on the above aspects of malacocenosis, it is possible to use and compare historical data of their incidence as well as to compare the data with current research. The pond system affected by the declension has an important function in the landscape today. The first malacological researches in the Loucké ponds territory were conducted in 1954 and 1955 (Brabenec, 1954, Ložek, 1964). Detailed survey was conducted by Macha (1978, 1979) who found 29 aquatic species (12 Bivalvia and 17 Gastropoda) and 19 land species of molluscs. This research was followed by the authors' survey in 2006, 2007 and 2013 which confirmed the presence of 48 molluscs species altogether (42 Gastropoda and 6 Bivalvia), from which 21 species were aquatic molluscs and 27 species were land molluscs.